METODE SPATIAL DURBIN MODEL UNTUK ANALISIS DEMAM BERDARAH DENGUE DI KABUPATEN BANTUL - Marthin Luter Laia; Rahmat Deswanto; Erma Shofi Utami; Rokhana Dwi Bekti (Jurnal Nasional Teknologi Terapan (JNTT), 2019)
Dengue Hemorrhagic Fever (DHF) is an infectious disease caused by the dengue virus which is transmitted through the bite of the Aedes aegepty and Aedes albopictus mosquitoes which are widespread in homes and public places throughout the territory of Indonesia. The high number of DHF cases in Bantul Regency, Indonesia is an indication that eradication of Aedes aegepty mosquitoes and Aedes albopictus mosquitoes has not succeeded in the Bantul Regency. Spatial Regression is an analysis that evaluates the relationship between one variable with several other variables by providing spatial effects in several locations that are the center of observation. Three type of models are Spatial Autoregressive Model (SAR), Spatial Error Model (SEM), and Spatial Durbin Model (SDM). This study uses secondary data in 2017 in Bantul Regency, Special Region of Yogyakarta, Indonesia. The dependent variable is DHF cases and the independent variables are medical personnel and health facilities in each sub-district. The spatial model used is SDM. Based on Moran’s I test, there was a spatial autocorrelation about DHF among sub-district, so the spatial model can be used. The durbin spatial model gives the result that all estimation parameters in SDM model have  P value less than α = 5%, so that medical personnel and health facilities significantly affect dengue cases in Bantul Regency. Keywords: dengue hemorrhagic fever, moran’s I test, spatial durbin model.